Novel ITGB2 Mutation Is Responsible for a Severe Form of Leucocyte Adhesion Deficiency Type 1. - Bouhouche, Ahmed; Tabache, Yasmin; Askander, Omar; Charoute, Hicham; Mesnaoui, Nada; Belayachi, Lamiae; El Hafidi, Naima; Hardizi, Houyam; El Fahime, Elmostafa; Erreimi, Naima; Barakat, Abdelhamid; Khattab, Mohammed; et al. (BioMed Research International, 2022)
Leukocyte adhesion deficiency type 1 (LAD1) is a rare autosomal recessive hereditary disorder characterized by recurrent infections, impaired pus formation, delayed wound healing, omphalitis, and delayed separation of the umbilical cord as hallmark features of the disease. It results from mutations in the integrin β2 subunit gene ITGB2, which encodes the integrin beta chain-2 protein CD18. In this study, we aimed to investigate the case of a five-month-old boy who presented with a clinical phenotype and flow cytometry results suggesting LAD1 disease. Sanger sequencing of all exons and intron boundaries of ITGB2 identified a novel in-frame deletion in exon 7 (ITGB2 c.844_846delAAC, p.Asn282del) in the patient. The p.Asn282del mutation was heterozygous in the child's parents, whereas it was absent in the 96 control individuals from North Africa. This variant was evaluated by two in silico mutation analysis tools, PROVEAN and MutationTaster, which predicted that the mutation was likely to be pathogenic. In addition, molecular modeling with the YASARA View software suggested that this novel mutation may affect the structure of integrin beta-2 and, subsequently, its interaction with integrin alpha-X. In summary, we report a novel pathogenic mutation p.Asn282del associated with LAD1 that expands the mutation diversity of ITGB2 and suggest the combination of flow cytometry and ITGB2 sequencing as a first-line diagnostic approach for LAD disease.